Survivors' Decision-Making around Legal Initiation for Historic CSA: An Interpretative Phenomenological Analysis. Issue 4 (19th May 2021) - Plastock, Hope; Bruce, Caroline; White, Naomi
ABSTRACT: Research shows disclosure of CSA is influenced by interpersonal, intrapersonal and systemic factors, but there is limited understanding of factors that may influence survivors' decisions as to whether to initiate legal proceedings against perpetrators or not. This understanding is necessary to support CSA survivors who may wish to pursue criminal conviction. This study aimed to qualitatively explore decision-making around legal initiation of historic abuse for adult survivors of CSA. Participants were attending psychological trauma services in Scotland and were identified for the study via treating clinicians. Seven participants engaged in individual semi-structured interviews. Data were generated using interpretative phenomenological analysis. Two main themes emerged: 1) awareness and preparedness for the legal process and 2) weighing up the possible outcomes of legal initiation. Six subordinate themes were identified. Like decision-making around disclosure, barriers and facilitators exist to legal initiation. Similar barriers included fear of harm and the impact of trauma on perceptions of self, others and systems. Similar facilitators included supportive relationships and increased visibility of CSA prosecutions. Legal initiation may require a distinct foundation of supportive factors, including information about the legal process.